Captain January - Richards, Laura Elizabeth Howe, 1850-1943 (Salt Lake City, UT : Project Gutenberg, 2005)
"Captain January" by Laura Elizabeth Howe Richards is a children's novel published in 1891. The story follows a solitary lighthouse keeper on a Maine island who rescues and raises an orphaned baby girl named Star Bright after a shipwreck. Their peaceful life together faces upheaval when a wealthy woman arrives, claiming the child as her long-lost niece. This heartwarming tale explores themes of love, belonging, and sacrifice as Captain January must consider what's truly best for the girl he cherishes. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Captain_January_(novel)
Release date is 2005-03-01
Produced by Ketaki Chhabra, Wendy Crockett, and David Widger
Keywords: Orphans -- Juvenile fiction; Conduct of life -- Juvenile fiction; Children -- Conduct of life -- Juvenile fiction; Islands -- Juvenile fiction; Kindness -- Juvenile fiction; Ship captains -- Juvenile fiction; Students -- Juvenile fiction; New England -- Juvenile fiction; Intergenerational relations -- Juvenile fiction; Lighthouse keepers -- Juvenile fiction; Home schooling -- Juvenile fiction